TO THE PROBLEM OF ORGANIZATION OF GENERAL CULTURAL TRAINING OF THE FUTURE TEACHER (Pedagogy of Higher and Secondary Education, 2010)
This article is devoted to the substantiate of place and value of the general cultural preparation of future teacher as an integral process which is represented by the intercommu nication of subjects of educational process in higher pedagogical educational establishments.